EARLY KALAM AS RATIONALLY-SPECULATIVE THEOLOGY OF MUTAZYLITS - Лубська, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article reviews the development of kalam’s philosophy within the speculative theology of Islam, its main problem being investigated and determined by the method and general typing of mutazylit kalam.